Muslims: their religious beliefs and practices - Rippin, Andrew (Library of religious beliefs and practices, 2005)
This concise and authoritative guide provides a complete survey of Islamic history and thought from its formative period to the present day. It examines the unique elements which have combined to form Islam, in particular the Qu'ran and the influence of Muhammad, and traces the ways in which these sources have interacted historically to create Muslim theology and law, as well as the alternative visions of Islam found in Shi'ism and Sufism. Combining core source materials with coverage of current scholarship and of recent events in the Islamic world, Andrew Rippin introduces this hugely diverse and widespread religion in a succinct, challenging and refreshing way. Using a distinctive critical approach which promotes engagement with key issues, from fundamentalism and women's rights to problems of identity and modernity, it is ideal for students seeking to understand Muslims and their faith. The improved and expanded third edition now contains brand new sections on twenty-first century developments, from the Taliban to Jihad and Al-Qaeda, and includes updated references throughout.